THE BEING EXAMINED OF YESÂRÎ ÂSIM ARSOY'S HIS SONG IN HÜZZAM MAQAM NAMED “ÖMRÜM SENI SEVMEKLE NIHAYET BULACAKTIR” IN TERM OF THE PERFORMANCE STYLE DIFFERENCES FROM THREE SINGERS (YESÂRÎ ÂSIM ARSOY, MÜNIR NURETTIN SELÇUK, BEKIR SIDKI SEZGIN) - Koç, Ferdi (PEOPLE: International Journal of Social Sciences, 2017)
Yesârî Âsim Arsoy, one of the twentieth century's composers in Turkish music, has been one of the most important composers of the period due to his unique style and the different horizons he brings to music. Turkish music has been taught through the Meshk from past to today and passed on to future generations in this way. Therefore, from the time when a song has been composed, have come up the different copies in the different times. This reveals that art is a living object. Hence, there is a difference in performances between the period in which a song has been composed and the performances in the following periods. This is an important feature of Meshk's contribution to Turkish music. Knowing the differences in performance of a song in Turkish music has been affecting the styles of the performers positively. In consideration of this subject, Yesarî Âsım Arsoy's life, art and composing in summary will be told and also be examined the performance differences of his song named “Ömrüm seni sevmekle nihâyet bulacaktır” in hüzzam maqam, which had been sung by himself, Münir Nurettin Selçuk and Bekir Sıdkı Sezgin. They are the important soloists of different periods.